2011
DOI: 10.1016/j.tins.2011.06.003
|View full text |Cite
|
Sign up to set email alerts
|

An opportunistic theory of cellular and systems consolidation

Abstract: Memories are often classified as hippocampus-dependent or –independent, and sleep has been found to facilitate both, but in different ways. In this Opinion article, we explore the optimal neural state for cellular and systems consolidation of hippocampus-dependent memories that benefit from sleep. We suggest that these two kinds of consolidation, which are ordinarily treated separately, may overlap in time and jointly benefit from a period of reduced interference (during which no new memories are formed). Cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
255
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 226 publications
(279 citation statements)
references
References 123 publications
23
255
1
Order By: Relevance
“…Error bars represent ±1 SEM. Asterisks represent significance at P < 0.05. opportunistic manner (40), such as in times of low external input (i.e., during a quiet wake period or during sleep), as has been shown in auditory tone sequence learning (41), visual search (42), and pursuit motor tasks (43). In contrast, some nondeclarative information, such as our Primed condition here, mainly rely on sleep processes (5,44,45).…”
Section: Resultsmentioning
confidence: 68%
“…Error bars represent ±1 SEM. Asterisks represent significance at P < 0.05. opportunistic manner (40), such as in times of low external input (i.e., during a quiet wake period or during sleep), as has been shown in auditory tone sequence learning (41), visual search (42), and pursuit motor tasks (43). In contrast, some nondeclarative information, such as our Primed condition here, mainly rely on sleep processes (5,44,45).…”
Section: Resultsmentioning
confidence: 68%
“…Such an association would not be expected if the nap merely protected the memory from waking interference (31,32). Moreover, if the reduced interference during sleep only provided an enhanced opportunity for memory consolidation (as opposed to being a process unique to sleep), one would expect a correlation between the change in memory over the nap and time spent asleep, particularly SWS in which long-term potentiation may be inhibited (32,33). We did not find such an association, nor did the length of non-REM stage 2 correlate with sleep-dependent changes in memory.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that sleep supports transforming new experiences into long-term memories (i.e., consolidation) (Diekelmann & Born 2010). For declarative memory, i.e., explicit memory for events and facts, consolidation is demonstrated by decreased forgetting of information after a period of sleep, compared to an equivalent amount of time awake (Mednick et al, 2011). Furthermore, several pieces of evidence converge to suggest that improved memory retention is directly related to specific events during sleep including sleep spindles (bursts of fast, 12-15Hz thalamic activity) and slow oscillations (SO, high voltage up and down states <1Hz that reflect periods of neuronal spiking and neuronal silence, respectively).…”
Section: Introductionmentioning
confidence: 99%